Struktur Komunitas Semut (Hymenoptera : Formicidae) di Lahan Pertanian Organik dan Anorganik Desa Batur, Kecamatan Getasan, Kabupaten Semarang - Putra, Ivan Mahadika; Hadi, Mochamad; Rahadian, Rully (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Ants play an important role in terrestrial ecosystems, including in organic and inorganic farmland, as predators, scavengers, and their interaction with other organism. The objectives of this study were to compare the community structure and the role of the ant in organic and inorganic farmland, and also to determine soil abiotic factors in both farmland. The study was conducted in organic and inorganic chili crop land at Batur village, Getasan, Semarang. The sampling of ants was performed using pitfall traps and bait traps, and then the ants were identified. Data analysis used is an abundance index, diversity index, evenness index, Hutchinson test and similarity index. The results showed that the number of species and the number of individual of ants in organic farm were higher (45 individuals, 8 species) than inorganic farm (35 individuals, 6 species). Diversity index of ant species in both farmlands were categorized moderate with the index value of 1.92 and 1.42. Statistically, there were no significant differences in species diversity of ants in organic and inorganic farmland. There were five dominant species in organic field and three dominant species in inorganic field. Ants that predominate in both farmlands were Iridomyrmexsp, Tetramorium sp, Solenopsisgeminata, Odontoponeradenticulata and Diacammasp. The similarity of ant communities between organic and inorganic farmland showed high value of similarity index (IS) which was 85.7%. Statistically, abiotic factors showed that there were significantly different of some abiotic factors in both farmlands, the content of carbon, phospor, organic matter and c / n ratio.Â Keywords: community structure of ants, agricultural ecosystems